2015
DOI: 10.1007/s11367-015-0926-3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental product declarations entering the building sector: critical reflections based on 5 to 10 years experience in different European countries

Abstract: Purpose Growing awareness of the environmental performance of construction products and buildings brings about the need for a suitable method to assess their environmental performance. Life cycle assessment (LCA) has become a widely recognised and accepted method to assess the burdens and impacts throughout the life cycle. This LCA-based information may be in the form of environmental product declarations (EPD) or product environmental footprints (PEF), based on reliable and verifiable information. All of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 20 publications
(27 reference statements)
0
70
0
6
Order By: Relevance
“…This led to the emergence of EPD programs (mostly in Europe, Canada and the US) that started developing and publishing specific methodological frameworks for product categories, called PCRs (Product Category Rules). In 2015, (Passer et al, 2015) state that more than 28 EPD programs exist worldwide referring to ISO 14025" (…), providing more than 2256 PCR documents and more than 3600 EPDs (see (Passer et al, 2015(Passer et al, , p. 1201). Yet, the growing number of LCA studies for construction materials also revealed the need to further develop the method (Abd Rashid and Yusoff, 2015;Augiseau and Barles, 2017;Buyle, Braet and Audenaert, 2013;Petek Gursel et al, 2014;van den Heede and Belie, 2012).…”
Section: Lca -Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This led to the emergence of EPD programs (mostly in Europe, Canada and the US) that started developing and publishing specific methodological frameworks for product categories, called PCRs (Product Category Rules). In 2015, (Passer et al, 2015) state that more than 28 EPD programs exist worldwide referring to ISO 14025" (…), providing more than 2256 PCR documents and more than 3600 EPDs (see (Passer et al, 2015(Passer et al, , p. 1201). Yet, the growing number of LCA studies for construction materials also revealed the need to further develop the method (Abd Rashid and Yusoff, 2015;Augiseau and Barles, 2017;Buyle, Braet and Audenaert, 2013;Petek Gursel et al, 2014;van den Heede and Belie, 2012).…”
Section: Lca -Methodsmentioning
confidence: 99%
“…Life Cycle Assessment (LCA) is decision support tool frequently used and well established to promote sustainable management as well as sustainable construction. International standards for LCA have been developed and the database for construction materials is constantly growing (Passer et al (2015). In many countries, this data is used in building labelling and certification schemes for sustainable construction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, there has been a high interest in the assessment and certification of construction-related materials through EPDs [24][25][26]. Moreover, green-building certification schemes (GBCS) such as the ones of the German Sustainable Building Council (DGNB) [27], the British Sustainability Assessment Method for Buildings (BREEAM) [28] or the United States (US) Leadership in Energy and Environmental Design (LEED ® ) v4 [29], recognize the use of EPDs for the disclosing of the environmental information of construction products.…”
Section: Sector-specific Examplementioning
confidence: 99%
“…LCA software programs in architecture became common in the last decade as environmental data on building material was increasingly available in the form of Environmental Product Declarations (EPDs) (Passer et al, 2015) or national databases. Institutions provide open access to databases like Ökobau.dat (BBSR, 2016) and Wecobis (Haas & Asam, 2014) and with knowledge on the method of LCA, the data can be linked to the building substance.…”
Section: Lca Toolsmentioning
confidence: 99%